1991
DOI: 10.1111/j.1439-0507.1991.tb00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of human granulocyte colony‐stimulating factor (hG‐CSF) on Cryptococcus and Aspergillus infections in normal and immunosuppressed mice

Abstract: Summary. Prophylactic treatment with human granulocyte colony‐stimulating factor (hG‐CSF) affords significant protection against systemic aspergillosis or pulmonary aspergillosis in neutropenic (cyclophosphamid‐treated) mice but not in cortisone‐treated animals. Cryptococcosis does not respond to hG‐CSF therapy. Our data show that granulocytes play an important role in the immune defense against aspergillosis, but not against cryptococcosis. Combined treatment using hG‐CSF and conventional antimycotics shows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(14 citation statements)
references
References 26 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…Studies of immunocompromised human subjects and experimental animals have established that neutrophils are essential for preventing fungal dissemination from the lung and for resolving this devastating complication when it occurs (19,42,55). Macrophages are further capable of phagocytosing smaller fungal forms (conidia and small hyphae) and killing them through the oxidative burst and other mechanisms (53,56).…”
mentioning
confidence: 99%
“…Studies of immunocompromised human subjects and experimental animals have established that neutrophils are essential for preventing fungal dissemination from the lung and for resolving this devastating complication when it occurs (19,42,55). Macrophages are further capable of phagocytosing smaller fungal forms (conidia and small hyphae) and killing them through the oxidative burst and other mechanisms (53,56).…”
mentioning
confidence: 99%
“…The in vitro data convincingly show the favorable impact of IFN-γ on neutrophil and macrophage handling of Aspergillus microconidia and hyphae alone or in combination with G-CSF [31,32] or GM-CSF [39,40]. The improved scavenger innate immune cell antifungal responses are due to 1) augmented neutrophil oxidative killing of A. fumigatus hyphae; 2) prevented corticosteroidmediated suppression of neutrophil killing of fungal hyphae; and 3) enhanced killing of A. fumigatus hyphae by human monocytes [31,32,39,40,47]. Data in mouse models using cytokine depletion, gene knockout mice, and administration of exogenous cytokines have been instrumental in establishing the conceptual basis for immunotherapy in invasive mycoses and in paving the way to early clinical trials [48][49][50].…”
Section: Ifn-γmentioning
confidence: 86%
“…In cyclophosphamide-treated neutropenic mice, human G-CSF was shown to provide significant protection against aspergillosis, whereas this benefit was not evident in cortisone-treated animals [31]. Another study showed prevention of corticosteroid-induced suppression of hyphal damage when neutrophils were pretreated with G-CSF [32].…”
Section: G-csfmentioning
confidence: 98%
“…Expression of these cytokine genes is controlled by the transcription factors NF-B (Zhao and Wu, 2008), AP-1 (Toyotome et al, 2008) and IRF3 and the expression of several cytokines changes significantly under immunosuppressive conditions with cortisol (Duong et al, 1998;Balloy et al, 2005). Among the list of induced cytokines a dramatic effect of TNF-␣ (Mehrad et al, 1999), G-CSF/GM-CSF (Schelenz et al, 1999;Polak-Wyss, 1991) and IL-8/KC/MIP-2 (Mehrad et al, 2002;Braedel et al, 2004) in terms of fatal outcome when the particular factor was missing has been described. As one probable explanation for the increased susceptibility under these conditions it was shown in the above mentioned studies that cell recruitment, mainly of neutrophils, was significantly hampered.…”
Section: Alveolar Macrophages (Ams)mentioning
confidence: 97%